Pregnancy planning, timing, happiness and depressive symptoms among low-income women living with and without HIV. (27th May 2018) - Polansky, Marcia; Singh, Hardeep; Gao, Yang; Aaron, Erika
Abstract: Objective: This study assessed associations of sociodemographic factors and pregnancy intent and wantedness with pregnancy happiness and prenatal depressive symptoms and the relationship between prenatal depressive symptoms and pregnancy happiness. Background: Depression is the leading cause of disability world-wide and more so for women. Women are most likely to experience depression in their child bearing years, including during pregnancy. Untreated prenatal depression, associated with unwanted pregnancies endangers the health and wellbeing of the mother and her child. Research on the association of prenatal depression with pregnancy happiness among women with low incomes in the U.S.A. is limited. For women living with HIV, associations among family planning factors, pregnancy feelings and prenatal depression have been understudied. Methods: Sixty-four women living with HIV and 194 HIV-negative low-income pregnant women receiving care in a public university-based ob-gyn clinic with integrated HIV-care in Philadelphia between 2009 and 2012 participated in the study. The women completed a questionnaire on sociodemographic and pregnancy factors and the Center for Epidemiological Studies Depression Scale (CES-D). The independent associations of sociodemographic and pregnancy factors with pregnancy happiness and associations of these factors and pregnancy happiness with the CES-D were assessed using multivariable linear regressions. Results: Women who felt the pregnancy was too soon were less happy being pregnant ( p < 0.01). Prenatal depressive symptoms were inversely associated with happiness with being pregnant and completing high school ( p < 0.001 for both). Conclusion: Health care professionals need to provide reproductive counselling and mental health for prenatal depression should explore feelings about being pregnant and being a mother.